Toothpaste use protocol with dental bleaching for a conservative treatment: Case reports - Waldemir F. Vieira-Junior; Thayla H. N. Gouveia; Bruna G Silva; Vanessa C. P. S. Bueno; Flávio H. B. Aguiar; Débora A. N. L. Lima (Wolters Kluwer Medknow Publications, 2017)
In-office bleaching is a treatment based on products that contain hydrogen peroxide (HP) while demonstrating whitening effectiveness. HP could promote alterations to surface morphologies and properties of dental tissues. The objective was describe a toothpaste protocol associated to bleaching therapy to promote a safer approach. Patient 1 (male) and Patient 2 (female) were attended, and toothbrushing (twice a day) with a dentifrice containing bioactive glass (BG) (NovaMin™) and fluoride was indicated before and during the treatment. Three bleaching sessions were made in cases, at intervals of 7 days. The gels used were 35% HP (Patient 1) and 35% HP supplied with calcium (Patient 2). The effectiveness of bleaching treatment was observed in both cases (Vita scale), with an esthetic self-acceptance. Sensitivity associated with the procedure was not reported. The indication of BG-based toothpaste is relevant in relation to enamel properties and did not affect the whitening effectiveness of dental bleaching.